IMPLEMENTATION OF ARGUMENT-DRIVEN INQUIRY (ADI) LEARNING MODELS ON ENVIRONMENTAL POLUTION TOPIC TO ENHANCE SEVENTH GRADE STUDENTS’ LEARNING OUTCOMES - Endang Deciku; Monica Prima Sari (ISER (Indonesian Science Education Research), 2023)
Science lessons are designed to help students understand natural phenomena and how to live side by side with nature. To build up such understanding, students need to acquire sufficient inquiry skills as part of the expected learning outcomes. However, science learning outcomes of seventh graders at SMP Negeri 1 Payakumbuh for the academic year 2021/2022 are still below the minimum mastery criteria. From observation, we found that students do not participate actively in classroom teaching, teacher do not implement suitable learning model and do not use supporting instructional materials. Environmental pollution is one of the topics in secondary school science that could serve as a context for students to apply their knowledge and 4C skills. This study aims to see the effect of applying the Argument-Driven Inquiry (ADI) learning model assisted with ADI worksheet on science learning outcomes. This quasi-experiment research use Pretest-Posttest Control Group Design. Data were collected through multiple choice items and observation sheets, then analyzed with descriptive statistics. Our findings suggest that the use of ADI learning model influenced the science learning outcomes of seventh grade students of SMP Negeri 1 Payakumbuh. This is indicated by the 0.566 N-Gain of experimental class which is significantly higher than 0.290 of the control class